Origin country institutions and immigrant retirement timing - Olof Åslund; Axel Cronert (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2024)
We study how immigrants' retirement expectations and behavior are affected by formal retirement institutions in their country of origin. The analysis combines newly collected world-wide gender-specific data on retirement age regulations with individual-level panel data from across Europe. Although the institutions in the country of residence are the most influential, immigrants are still considerably more likely to retire at an age that matches an institutionalized retirement age in their country of origin. The relative importance of the origin country institutions is highest for immigrants who arrived at a higher age, those who have low financial literacy, and those for whom pension rights are internationally portable. These results indicate that mechanisms related to both social norms and economic incentives are at work. Our findings demonstrate how immigrants' beliefs and behavior are influenced not only by informal cultural institutions stemming from their country of origin (documented in previous research), but also by specific and alterable formal institutions determined by legislative processes.
Keywords: 330